ChemInform Abstract: Photoluminescence and Thermal Stability of Mn2+ Co‐Doped SrSi2O2N2:Eu2+ Green Phosphor Synthesized by Sol—Gel Method. Issue 18 (6th May 2014) - Liu, Jiaqing; Wang, Xiaojun; Xuan, Tongtong; Li, Huili; Sun, Zhuo
Abstract Eu2+ and Mn2+ co‐doped SrSi2O2N2 phosphors are prepared via a sol‐gel method using HNO3 solutions of SrCO3 and Eu2O3, EtOH solutions of Mn(OAc)2 and Si(O‐Et)4 (TEOS), and α‐Si3N4 and citric acid at 80 °C followed by drying the resulting gel (200 °C, 4 h) and calcination under reducing atmosphere (1400 °C, 6 h, 5% H2/N2).